Neurolaw and Criminal Jurisprudence in India - Mishra, Pragya (Taylor & Francis Group, 2025)
This work explores the transformative potential of neuroscience in reshaping India's criminal justice system. It explores the complex terrain of neurolaw, examining its implications for criminal responsibility, rehabilitation, and the foundations of legal thought. It proposes innovative approaches to longstanding legal and ethical dilemmas
Description based on publisher supplied metadata and other sources